Erasing graphite portraits a metaphor to memory loss from Alzheimer's disease - Vaño, Gabriela Isobelle Niña N.; Cabangis, Benjamin; Olazo, Jonathan Emmanuel (Quezon City College of Fine Arts, University of the Philippines Diliman)
This thesis aimed to show the process of erasure, as a metaphor to the destructive outcome of Alzheimer's Disease - specifically, the eventual loss of recognition of family members. It used my experience, watching my grandmother, Caridad Nazareno, lose her memories to this disease. The output was a series of erased graphite portraits set in my grandmother's point of view. I used Ferdinand de Saussure's model of Semiotics, and Gentner & Bowdle's Psychology of Processing Metaphors to tie together the following concepts : Drawing and the creation of memory; and, erasure and the loss of memory due to Alzheimer's Disease. In this thesis, Drawing was only a precursor to my exploration of the concept of Erasure. I tried to show the process of Erasure as evidence to the pain in forgetting, and the final series of erased portraits as a visual manifestation of a perverse palimpsest. The final output of this thesis was a series of eleven, erased, full body, graphite portraits, and a video documentation of the process of their erasure. This thesis was an attempt to depict my family's gradual metaphorical death in the memory of my grandmother, subtly encountered in the final manifestation of the wo
Thesis (Bachelor of Fine Arts in Studio Arts)--University of the Philippines Diliman
Bibliography : leaves 45-
Keywords: Alzheimer's disea; Portrai